Basic Concept and History of Inheritance Law in Indonesia - Muarafa Nur Afif; Moh. Wahyu (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
Abstract: Inheritance law is a law which is also referred to as the word faraid, which means distribution of inheritance of property if the death of the testator occurs. This research aims to understand the basic concepts of inheritance law and the history of inheritance law in Indonesia. This research uses the literature study method. The research results show that inheritance law is the law that regulates the distribution of inheritance from heir to heir. The basis for the legal position of inheritance is based on the Qur’an and the hadith of the Prophet Muhammad SAW. The history of inheritance law starts from the Jahiliyah era or before the arrival of Islam, the Islamic period, inheritance law before independence in Indonesia and after Indonesian independence there was Islamic law legislation through law number 7 of 1989 concerning Religious Courts which then gave birth to Presidential Instruction number 1 of 1991 which known as a compilation of Islamic law. In conclusion, the inheritance law in Indonesia has a long history, and it was finally established in the compilation of Islamic law. Keywords: Inheritance; Basic Concepts; History Abstrak: Hukum waris merupakan hukum yang juga disebut dengan istilah kata faraid yang berarti pembagian merupakan pewarisan harta benda apabila terjadi kematian pada pewaris. Tujuan penelitian ini untuk mengetahui konsep dasar hukum waris dan sejarah hukum waris di Indonesia. Penelitian ini menggunakan metode studi pustaka. Hasil penelitian, Hukum waris merupakan hukum yang mengatur pembagian warisan dari pewaris ke ahli waris. Dasar kedudukan hukum mawaris berdasarkan pada Alquran serta hadis nabi Muhammad SAW. Sejarah hukum waris dimulai dari sejak zaman Jahiliyah atau sebelum kedatangan Islam, masa keislaman, hukum waris sebelum kemerdekaan di Indonesia dan pasca Indonesia merdeka terjadi legislasi hukum Islam melalui undang-undang nomor 7 tahun 1989 tentang Peradilan Agama yang kemudian lahirnya Inpres nomor 1 tahun 1991 yang dikenal sebagai kompilasi hukum Islam. Kesimpulannya Hukum Waris di Indonesia memiliki sejarah yang panjang hingga akhirnya ditetapkan dalam Kompilasi hukum Islam. Kata Kunci: Kewarisan; Konsep Dasar; Sejarah